2000
DOI: 10.1002/1099-1409(200009/10)4:6<611::aid-jpp230>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular electronic structure of subphthalocyanine macrocycles

Abstract: Quantum chemical calculations at semiempirical (MNDO methods) and ab initio (6-31G and STO-3G basis ses) levels have been performed on boron(III) subphthalocyanines 1-10. Theoretical calculations predict a cone-shaped structure for these compounds independently of the kind of peripheral substitution and even of compositional changes in the central region of the macrocycle (for example, substitution of the boron atom by two hydrogens). The theoretical calculations are in excellent agreement with previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 49 publications
8
35
0
Order By: Relevance
“…Oxidation and reduction give rise to the lengthening and shortening, respectively, of the BCl bond length. A possible broad explanation for this fact is that the addition of one or more electrons increases the electron density in the macrocycle (because the redox processes in SubPc mainly involve the macrocycle but not the Cl axial substituent 19–21) and, consequently, leads to an increase of the repulsion between the Cl atom and the macrocycle that are both negatively charged. Because Δ d (+1→+2)BCl/Δ d (0→+1)BCl and Δ d (+1→+2)BCl/Δ d (0→+1)BCl are less than 2, it can be concluded that these repulsive effects are not additive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidation and reduction give rise to the lengthening and shortening, respectively, of the BCl bond length. A possible broad explanation for this fact is that the addition of one or more electrons increases the electron density in the macrocycle (because the redox processes in SubPc mainly involve the macrocycle but not the Cl axial substituent 19–21) and, consequently, leads to an increase of the repulsion between the Cl atom and the macrocycle that are both negatively charged. Because Δ d (+1→+2)BCl/Δ d (0→+1)BCl and Δ d (+1→+2)BCl/Δ d (0→+1)BCl are less than 2, it can be concluded that these repulsive effects are not additive.…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained taking into account that the reductive electrons are mostly located in the macrocycle as suggested by the spatial distribution of the LUMOs (see Refs. 19–21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,16] Both approaches indicate an excess of electronic charge on the electronegative atoms which surround the electron-deficient boron. This charge is compensated by an electron deficit which is mainly localized on the six central carbon atoms (Figure 4).…”
mentioning
confidence: 99%
“…results in a calculated permanent axial dipole moment of 0.95 e ä pointing away from the Cl, the magnitude of which compares well to a measured value of 1.1 e ä and to the value of 1.2 e ä predicted by AM1 calculations. [16] Each SubPc molecule is presumably bound to the substrate by a Cl ± Ag interaction and by electrostatic attraction of its polar charge distribution with the induced counter polarization of the metallic substrate. On the basis of XPS and UPS data [17] we conclude that the SubPc is adsorbed intact with the Cl pointing towards the substrate.…”
mentioning
confidence: 99%